Dancing shoes - Streatfeild, Noel (New York Random House, 2019)
When their mother dies, two girls go to live with their cousin Dulcie, whose mother runs a dancing school.
Copyright renewed 1985
108499
Keywords: Dance -- Juvenile fiction; Orphans -- Juvenile fiction; Great Britain; Juvenile works; Fiction